The oxidative stress response of Streptococcus pneumoniae: its contribution to both extracellular and intracellular survival - Hernandez-Morfa, Mirelys; Olivero, Nadia B.; Zappia, Victoria E.; Piñas, German E.; Reinoso-Vizcaino, Nicolas M.; Cian, Melina B.; Nuñez-Fernandez, Mariana; Cortes, Paulo R.; Echenique, Jose (Frontiers in Microbiology, 2023)
Streptococcus pneumoniae is a gram-positive, aerotolerant bacterium that naturally colonizes the human nasopharynx, but also causes invasive infections and is a major cause of morbidity and mortality worldwide. This pathogen produces high levels of H2O2 to eliminate other microorganisms that belong to the microbiota of the respiratory tract.However, it also induces an oxidative stress response to survive under this stressful condition. Furthermore, this self-defense mechanism is advantageous in tolerating oxidative stress imposed by the host's immune response.This review provides a comprehensive overview of the strategies employed by the pneumococcus to survive oxidative stress. These strategies encompass the utilization of H2O2 scavengers and thioredoxins, the adaptive response to antimicrobial host oxidants, the regulation of manganese and iron homeostasis, and the intricate regulatory networks that control the stress response. Here, we have also summarized less explored aspects such as the involvement of reparation systems and polyamine metabolism. A particular emphasis is put on the role of the oxidative stress response during the transient intracellular life of S. pneumoniae, including coinfection with influenza A and the induction of antibiotic persistence in host cells.